A STUDY ON BEHAVIORAL MUSIC AND MUSICAL BEHAVIOR IN DEVELOPING CHARACTER EDUCATION THROUGH MUSIC EDUCATION - Esy Maestro (International Conference on Languages and Arts, 2014)
Character education issues are booming to be discussed by Indonesian people lately. In this paper, I want to take part in this positive trend, which also describes how the relationship between character education with the field of music. The selected context in the discourse of character education is the problem of behavioral music and musical behavior, the latter study has contributed in the development of educational music, both reviewed in the development of affective values ​​and skill development in the field of music. I would like to convey the message that the message that the music also has a close connection with character education. Beliefs about the existence of a significant relationship between music and character education partly motivated by the concept of music education is built from behavior that is consistent with the character education.   Keywords: Behavioral Music; Musical Behavior; Character Education.